Optimizing Student Digital Literacy Through SPADA (Online Learning System) In Graph Theory Courses - Vera Septi Andrini; Erdyna Dwi Etika; Reza Dimas Pravangasta Perdana (Departement of Mathematics Education, 2023)
Online learning has been carried out simultaneously since the Covid-19 Pandemic but there are various problems experienced by students. SPADA is an online learning system initiated by the Ministry of Education and Culture with various features that make it easier for students to learn. This study aims to determine the effect of learning through SPADA on digital literacy in graph theory courses through SPADA. This type of research was ex-post facto, on the basis of the consideration that the researcher does not give treatment to the independent variables studied because the events have already taken place (after the fact). The results are analyzed using descriptive analysis and inferential analysis (F-test). The population is the class of 2020 which is currently programming a graph theory course. With Slovin formula, a minimum sample of 54 students is obtained. The instruments used were student learning outcomes tests and questionnaires. The research results obtained are probability values (Sig. F Change) = 0.000. Because the value of sig.F Change <0.05, it can be concluded that H0 is rejected and H1 is accepted. This means that there is a significant direct effect between learning graph theory through SPADA on digital literacy of Mathematics Education students.